Methanol carbonylation to acetaldehyde on Au particles supported by single-layer MoS2 grown on silica. (24th December 2021) - Almeida, Kortney; Chagoya, Katerina; Felix, Alan; Jiang, Tao; Le, Duy; Rawal, Takat B; Evans, Prescott E; Wurch, Michelle; Yamaguchi, Koichi; Dowben, Peter A; Bartels, Ludwig; Rahman, Talat S; et al.
Abstract: Homogenous single-layer MoS2 films coated with sub-single layer amounts of gold are found to isolate the reaction of methanol with carbon monoxide, the fundamental step toward higher alcohols, from an array of possible surface reactions. Active surfaces were prepared from homogenous single-layer MoS2 films coated with sub-single layer amounts of gold. These gold atoms formed clusters on the MoS2 surface. A gas mixture of carbon monoxide (CO) and methanol (CH3 OH) was partially converted to acetaldehyde (CH3 CHO) under mild process conditions (308 kPa and 393 K). This carbonylation of methanol to a C2 species is a critical step toward the formation of higher alcohols. Density functional theory modeling of critical steps of the catalytic process identify a viable reaction pathway. Imaging and spectroscopic methods revealed that the single layer of MoS2 facilitated formation of nanoscale gold islands, which appear to sinter through Ostwald ripening. The formation of acetaldehyde by the catalytic carbonylation of methanol over supported gold clusters is an important step toward realizing controlled production of useful molecules from low carbon-count precursors.